Regulatory Responses to Data Breaches: Evaluating the Effectiveness of GDPR and CCPA in Consumer Protection - Leonardo W Ou (International Journal of Social Sciences and Public Administration, 2025)
In the digital age, data breaches have become a significant threat to consumer privacy, prompting the implementation of stringent data protection regulations worldwide. This paper evaluates the effectiveness of two prominent regulatory frameworks, the General Data Protection Regulation (GDPR) in the European Union and the California Consumer Privacy Act (CCPA) in the United States, in safeguarding consumer data and responding to data breaches. Through a comparative analysis of their key provisions, enforcement mechanisms, and real-world impacts, the study examines how these regulations address consumer rights, data access, and control. The research employs a mixed-methods approach, analyzing case studies of major data breaches under each framework, including the 2018 British Airways breach (GDPR) and the 2020 Zoom breach (CCPA). Findings reveal that GDPR, with its broader scope, stringent enforcement, and higher penalties, offers a more comprehensive and proactive approach to data protection compared to the CCPA, which is more localized and reactive. The study highlights the challenges and limitations of each framework, emphasizing the need for ongoing refinement to address emerging technological and cybersecurity threats. The paper concludes that GDPR serves as a global benchmark for data protection, while the CCPA represents a significant but narrower step toward enhancing consumer privacy in the U.S. Future research should explore the adaptability of these regulations to new technologies and their socio-economic impacts on businesses, particularly small and medium-sized enterprises.